Exploration or exploitation? Small firms' alliance strategies with large firms - Yang, Haibin; Zheng, Yanfeng; Zhao, Xia (Strategic Management Journal, 2014)
How do small firms manage their alliance strategies with large firms? This study compares the relative impacts of exploration and exploitation alliances with large firms on small firms' valuation. Integrating the literatures on the exploration/exploitation paradigm and alliance governance, we argue that exploitation alliances with large firms will on average generate higher values for small firms than exploration alliances with large firms due to a heightened risk of appropriation in exploration alliances. However, if small firms can manage their alliances with large firms via proper alliance governance, they will increase their valuations from exploration alliances with large firms. Analyses of the U.S. biopharmaceutical industry from 1984 to 2006 largely support our hypotheses . Copyright © 2013 John Wiley & Sons, Ltd.